The Last Night of Freedom: Consumerism, Deviance and the "Stag Party". Issue 7 (3rd July 2017) - Briggs, Daniel; Ellis, Anthony
ABSTRACT: This article offers an ethnographic examination of the stag party phenomenon in the United Kingdom. Stag parties have become socially expected as a rite of passage, pre-marriage celebration for men that usually involves excessive alcohol consumption and engagement in deviant, potentially harmful, behavior. These events produce a shift in time and space, and together with group expectations for celebration, increase the impetus for excessive consumption. Our contention is that excessive consumption of alcohol and deviant behavior that often takes place are partially rooted in commercial ideology, which has become firmly embedded in the attitudes of young British men.